Effect of CNT concentration on mechanical properties and microstructure evolution of grout - Li, Peng; Luo, Xianzhe; Wang, Pengyu; Wang, Kai; Du, Yue; Zhang, Qiang (Frontiers in Materials, 2025)
In order to elucidate the mechanism of carbon nanotubes (CNTs) in cementitious materials and their effects on microstructural and mechanical properties, this study combines in-house experiments with PFC2D particle flow numerical simulations to systematically analyse the macromicro-mechanical behaviours of the grouted nodular bodies under different CNTs concentrations. Uniaxial compression tests were carried out on specimens constructed from crushed aggregate with a fractal dimension of 2.415, and the results showed that CNTs incorporation significantly enhanced the compressive strength and strain capacity of the nodules, with the optimal performance at a concentration of 0.05% CNTs, and the peak strength and peak strain were increased by 14.9% and 9.7% compared with those of the unincorporated specimens, respectively. Numerical simulation results showed that the maximum deviation of peak strength and strain between simulation and test was 2.01% and 2.96%, respectively, which verified the reliability of the model. Microanalysis showed that 0.05% CNTs optimised the crack extension path and force chain distribution by enhancing the bonding force at the cemented particle-aggregate interface, and inhibited the penetration of shear cracks, while too high a concentration (e.g., 0.15%) weakened the interface due to the agglomeration of CNTs, which exacerbated the force chain rupture and structural instability. This study reveals the regulation mechanism of CNTs concentration on the mechanical properties of the grouted rock body, which provides a theoretical basis for the efficient reinforcement of the crushed surrounding rock in engineering.